How Can the Water Springs Be Sustainable?: An Overview of Cross-Time Environmental Communication Strategies on the Village-Owned Enterprise in Indonesia - Moch. Adi Surahman; Maulina Pia Wulandari; Suryadi (GoAcademica Research & Publishing, 2021)
This research has an interpretive social science paradigm which implies an exploratory form. The purpose of the study was to find out various potential efforts carried out by the management of the Barokah Village Owned Enterprise (BUMDes) as an environmental communication strategy for conserving the Sira Springs in Putukrejo, Malang Regency. The research data collection method was a combination of in-depth interviews, partisan field observations, and documentation. Analysis of research data is descriptive-qualitative and uses interactive analysis techniques as a reference. Application of triangulation includes size, time, and observer. The technique of collecting informant data is purposively against representatives of village government apparatus, BUMDes administrators, and managers of springs. The study results reveal that the environmental communication strategy of BUMDes Barokah as an effort to preserve Sira springs is currently achieving a Strengthening Strategy as Focht’s preposition strengthened by Tyson & Unson (2006). This is due to the decreasing controversy among them and the relatively high level of public and scientific consensus that has been achieved since the beginning of Sira resource management through the establishment of BUMDes. This strengthening strategy is mainly through Word of Mouth, special performances or events, and mass communication and new media involving the participation of the local community. They also relatively understand the axioms of environmental communication as explained by Jurin, Roush, & Danter (2010) in their daily practice. The potential efforts of the BUMDes Barokah management, together with the work unit groups under its auspices and the Putukrejo village community, which are closely related to local characteristics, are densely discussed in this article.